2003
DOI: 10.1038/sj.onc.1207328
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of the retinoid response gene TIG1 in prostate cancer correlates with methylation of the retinoic acid receptor beta gene

Abstract: Methylation of CpG islands and associated gene silencing may lead to malignant progression, but the mechanisms of CpG island methylation in cancer are unknown. The tazarotene-induced gene 1 (TIG1), also known as retinoid acid (RA) receptor-responsive 1 gene was first identified as an RA-responsive gene and was shown to be downregulated in prostate cancer. Here, we show that this downregulation is caused by the methylation of the promoter and CpG island of TIG1. TIG1 was methylated in 26 of 50 (52%) primary pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 41 publications
2
69
2
Order By: Relevance
“…Positive correlation between the methylation of TIG1 and RAR-beta was also observed in prostate cancer. 26 In our present study, we have also confirmed that the promoter hypermethylation of TIG1 is related to its gene silencing in prostate cancer cell lines. Therefore, these findings suggested that promoter hypermethylation is the major mechanism for TIG1 inactivation and the silencing of this potential tumor suppressor gene may be a critical step for cancer development in different tissues.…”
Section: Discussionsupporting
confidence: 84%
“…Positive correlation between the methylation of TIG1 and RAR-beta was also observed in prostate cancer. 26 In our present study, we have also confirmed that the promoter hypermethylation of TIG1 is related to its gene silencing in prostate cancer cell lines. Therefore, these findings suggested that promoter hypermethylation is the major mechanism for TIG1 inactivation and the silencing of this potential tumor suppressor gene may be a critical step for cancer development in different tissues.…”
Section: Discussionsupporting
confidence: 84%
“…While preparing this article, Tokumaru et al reported hypermethylation of the Tig1 gene in a variety of nonendometrial human cancer cell lines, with 17 of 25 (68%) of these lines having a methylated Tig1 (25), and Tig1 was noted to be methylated in clinical samples of prostate cancer (26) and a variety of human cancers (27)(28)(29). Taken together, Tig1 may function as a tumor suppressor gene and prevent carcinogenesis not only in endometrial cells but also in a variety of tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike detection of prostate cancer DNA using tests for methylation marks, DNA methylation biomarkers for prostate cancer prognosis are still limited. Methylation marks for EDNRB, RARb, RASSF1a, ERb, and TIG1 may be suitable for this unmet need as each has been correlated with known prognostic factors for primary prostate cancer, such as tumor stage and/or Gleason grade (22)(23)(24)(25)59). Indeed in 1 study, PTGS2 methylation marks in the localized prostate cancer predicted prostate cancer recurrence after radical prostatectomy, independently of tumor stage and Gleason grade (60).…”
Section: Discussionmentioning
confidence: 99%
“…Notably hypermethylation of the glutathione S-transferase P1 (GSTP1) gene occurs in approximately 90% of all prostate cancers and is an early event, with DNA methylation lesions common in prostate intraepithelial neoplasia, making this gene a useful marker for early prostate cancer detection (17,18). In addition to GSTP1, more than 40 genes have been reported to be targets of epigenetic gene silencing in prostate cancers (19) including adenomatosis polyposis coli (APC), Ras association domain family 1A (RASSF1A), prostaglandinendoperoxidase synthase 2 (PTGS2), multidrug resistance gene 1 (MDR1), retinoic acid receptor beta 2 (RARb2), tazarotene-induced gene-1 (TIG1), and oestrogen receptor-beta (ER-b), which have also been shown to be involved in tumor initiation and progression and have been correlated with clinicopathologic parameters (20)(21)(22)(23)(24)(25). A number of groups have also attempted to use combinations of genes to develop improved methylation-based tests for disease progression (26)(27)(28); however, no current epigenetic biomarker can predict disease aggressiveness or survival better than Gleason grade and serum PSA tests.…”
Section: Introductionmentioning
confidence: 99%